Gestational Diabetes Mellitus: Closely Monitored yet Ignored - Akhtar, Tasneem; Tasleem, Huma; Gulshan Ara Saeed; Jawad Zaka Khan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the perception and knowledge of women regarding gestational diabetes mellitus and to identify the barriers faced in acquiring health care and lifestyle modifications. Study Design: Mix Method Study. Place and Duration of Study: This study was carried out at Shifa College of Medicine and Shifa Foundation Community Health Centre, Islamabad Pakistan, from Jan to Jul 2020. Sixty women with gestational diabetes mellitus were recruited from a clinic in Shifa Foundation Community Health Centre. Methodology: A mix method study was carried out in Shifa international hospital. 60 patients suffering from gestational diabetes mellitus were recruited for the study in order to assess the awareness and knowledge of gestational diabetes mellitus among patients suffering from Gestational Diabetes Mellitus. Questionnaire based survey was carried out. Quantitative analysis was done using Microsoft excel. In the next phase. Four Focus group interviews were carried out by principal investigator in a selected area giving an ample amount of time for Focus Group Discussions. Perception of patients were inquired and predetermined questions were asked to guide the discussion. Data from each participant was tape recorded and transcribed using verbatim afterwards. Results: N=18(30%) of the population had much information on gestational diabetes mellitus while 24(40%) of them had some information, the rest had little or no information on it. A high percentage of respondents 21(35%) had a perception that gestational diabetes mellitus has future effects on child or Conclusion: The overall perception of women regarding gestational diabetes mellitus and its impact on their future generations